The effect of method of instruction given on muscle activation and kinematic during vertical and horizontal based strength training - Thariq Khan Azizuddin Khan (Tanjong Malim, 2019)
The effect of method of instruction given on muscle activation and kinematic during vertical and horizontal based strength training by Thariq Khan Azizuddin Khan